Effect of hypoxia and uremia on oxidative stress on erythrocytes from hemodialysis patients. (19th September 2022) - Dias, Gabriela F.; Tozoni, Sara S.; Bohnen, Gabriela; van Spitzenbergen, Beatriz A. K.; Grobe, Nadja; Nakao, Lia S.; Pecoits‐Filho, Roberto; Kotanko, Peter; Moreno‐Amaral, Andréa N.
Abstract: Oxidative stress (OS) is essential in uremia‐associated comorbidities, including renal anemia. Complications experienced by hemodialysis (HD) patients, such as hypoxemia and uremic toxins accumulation, induce OS and premature death of red blood cells (RBC). We aimed to characterize reactive oxygen species (ROS) production and antioxidant pathways in HD‐RBC and RBC from healthy controls (CON‐RBC) and evaluate the role of uremia and hypoxia in these pathways. ROS production, xanthine oxidase (XO) and superoxide dismutase (SOD) activities, glutathione (GSH), and heme oxygenase‐1 (HO‐1) levels were measured using flow cytometry or spectrophotometry in CON‐RBC and HD‐RBC (pre‐ and post‐HD), at baseline and after 24 h incubation with uremic serum (S‐HD) and/or under hypoxic conditions (5% O2 ). Ketoprofen was used to inhibit RBC uremic toxins uptake. HD‐RBC showed higher ROS levels and lower XO activity than CON‐RBC, particularly post‐HD. GSH levels were lower, while SOD activity and HO‐1 levels of HD‐RBC were higher than control. Hypoxia per se triggered ROS production in CON‐RBC and HD‐RBC. S‐HD, on top of hypoxia, increased ROS levels. Inhibition of uremic toxins uptake attenuated ROS of CON and HD‐RBC under hypoxia and uremia. CON‐RBC in uremia and hypoxia showed lower GSH levels than cells in normoxia and non‐uremic conditions. Redox mechanisms of HD‐RBC are altered and prone to oxidation. Uremic toxins and hypoxia play a role in unbalancing these systems. Hypoxia and uremia participate in the pathogenesis of OS in HD‐RBC and might induce RBC death and thus compound anemia. Significance statement: This study aimed to elucidate the mechanisms of redox imbalance that arise in erythrocytes in chronic kidney disease. Uremia and hypoxia can reduce the patient's antioxidant apparatus, leading to oxidative stress and compromising several physiological functions. This study may support future strategies to target oxidative stress pathways and improve the health of dialysis patients.